Ictal cardiovascular autonomic dysfunction during focal seizures induced by direct electrical stimulation: An observational study research protocol - Dmitry Zhuravlev; Anna Marchenko; Anastasia Skalnaya; Marina Lebedeva; Igor Trifonov; Flora Rider; Nikolay Ierusalimsky; Sabir Burkitbaev; Natalia Semenovykh; Roman Luzin; Mikhail Sinkin; Vladimir Krylov; et al. (PLoS ONE, 2025)
Introduction Autonomic symptoms, such as changes in heart rate, blood pressure, or respiration often accompany epileptic seizures and, in some cases, may be life threatening or even contribute to sudden death. However, autonomic changes during seizures with onset from certain brain areas are insufficiently understood. Intracranial direct electrical stimulation during stereoelectroencephalographic (SEEG) monitoring in surgical candidates allows researchers to investigate autonomic responses to induced seizures in conscious patients with known precise location of the electrodes. We aimed to identify the epileptogenic focus locations or brain structures associated with ictal cardiovascular autonomic dysfunction during focal seizures induced by direct electrical stimulation. Methods and analysis This is an observational study. In focal epilepsy patients undergoing presurgical evaluation with implanted intracranial SEEG electrodes, we will record heart rate (HR), beat-to-beat blood pressure (BP), and respiratory rate during the SEEG monitoring and stimulation conducted in accordance with the clinical needs. Tachycardia (HR > 100 bpm), bradycardia (HR < 60 bpm), hypertension (systolic or diastolic BP ≥ 140/90 mmHg), and hypotension (systolic or diastolic BP < 90/60 mmHg) during the first minute of induced clinical seizures will be considered as ictal cardiovascular autonomic dysfunction. We will use the chi-squared test to compare percentage of dysautonomia-associated seizures in the total number of induced seizures between cortical areas related to or interconnected with the central autonomic network and other cortical areas. Significance will be assumed for p-values < 0.05. At the time of submission, this study has enrolled thirteen patients and still on-going.